Faktor Penyebab Stunting Pada Anak: Tinjauan Literatur - Yanti, Nova Dwi; Betriana, Feni; Kartika, Imelda Rahmayunia (REAL in Nursing Journal, 2020)
Background: Stunting is defined as a short or very short body state caused by various factors. Objective: This article aims to review factors causing stunting, including mother`s knowledge and parenting style, nutrition intake, low birth weight (LBW), and family`s financial status. Method: This literature review was conducted through searching relevant evidences from electronic database (Google scholar) using the following keywords: "causes of stunting", and "factors of stunting" in Indonesian (Bahasa) and English. Twelve articles were selected based on the following inclusion criteria: the date of publication from 2009 to 2018, discussing the causes of stunting in the golden age of children, English and Indonesian articles, full text, open access, and academic journals. The articles were analyzed using matrix tables. Results: Knowledge of mother and parenting style, nutrition intake, LBW, and fincancial economic status are indicated as factors causing stunting in the golden age of children. Conclusion: The occurrence of stunting is very vulnerable at the golden age of children due to those mentioned factors. Programs designed to increase parents` knowledge such as antenatal care, nutrition intake for mother during pregnancy, nutrition intake for children, and parenting information are recommended.